Does green investment reduce carbon emissions? New evidence from partially linear functional-coefficient models - Zhe Huang (Heliyon, 2023)
Green investment (GI) has great potential to reach China's 'double carbon' target. However, it is still unknown what factors will govern the impact of GI on carbon emissions. This research relaxes the homogeneity and linearity assumed in traditional empirical models and adopts a newly developed partially linear functional-coefficient model to estimate the specific response function of GI on carbon emissions under regional heterogeneity. The results indicate that the role of GI plays a relatively greater role in the western and central regions than in the eastern regions. This highlights the latecomer advantage of the central and western regions under the 'double carbon' target. The beneficial effect of GI on carbon emission intensity is only apparent once the province's economic development level exceeds a certain threshold. For provinces with low GDP per capita, it is recommended to prioritize economic development. When the logarithm of the province's GDP per capita is higher than 9.70, we encourage strong GI. As the industrial structure continues to upgrade, the marginal effect of GI on carbon emissions will continue to increase after a key inflection point.